Bundle sheath extensions affect leaf structural and physiological plasticity in response to irradiance. (19th February 2019) - Barbosa, Maria Antonia M.; Chitwood, Daniel H.; Azevedo, Aristéa A.; Araújo, Wagner L.; Ribeiro, Dimas M.; Peres, Lázaro E.P.; Martins, Samuel C.V.; Zsögön, Agustin
Abstract: Coordination between structural and physiological traits is key to plants' responses to environmental fluctuations. In heterobaric leaves, bundle sheath extensions (BSEs) increase photosynthetic performance (light‐saturated rates of photosynthesis, A max ) and water transport capacity (leaf hydraulic conductance, K leaf ). However, it is not clear how BSEs affect these and other leaf developmental and physiological parameters in response to environmental conditions. The obscuravenosa ( obv ) mutation, found in many commercial tomato varieties, leads to absence of BSEs. We examined structural and physiological traits of tomato heterobaric and homobaric ( obv ) near‐isogenic lines grown at two different irradiance levels. K leaf, minor vein density, and stomatal pore area index decreased with shading in heterobaric but not in homobaric leaves, which show similarly lower values in both conditions. Homobaric plants, on the other hand, showed increased A max, leaf intercellular air spaces, and mesophyll surface area exposed to intercellular airspace ( S mes ) in comparison with heterobaric plants when both were grown in the shade. BSEs further affected carbon isotope discrimination, a proxy for long‐term water‐use efficiency. BSEs confer plasticity in traits related to leaf structure and function in response to irradiance levels and might act as a hub integrating leaf structure, photosynthetic function, and water supply and demand. Abstract : The presence of bundle sheath extension (BSEs) defines leaves as heterobaric, as opposed to homobaric leaves that lack them. Multiple functions have been proposed for BSEs, but their impact on different environmental conditions is still unclear. Here, we compared a tomato ( Solanum lycopersicum ) homobaric mutant lacking BSEs with its corresponding heterobaric wild type, grown under two irradiance conditions. We show that the presence of BSEs differentially alters various physiological and anatomical parameters in response to growth irradiance. We propose that BSEs could act as hubs coordinating leaf plasticity in response to environmental factors.